2020
DOI: 10.1038/s41467-020-19835-1
|View full text |Cite
|
Sign up to set email alerts
|

Valley interference and spin exchange at the atomic scale in silicon

Abstract: Tunneling is a fundamental quantum process with no classical equivalent, which can compete with Coulomb interactions to give rise to complex phenomena. Phosphorus dopants in silicon can be placed with atomic precision to address the different regimes arising from this competition. However, they exploit wavefunctions relying on crystal band symmetries, which tunneling interactions are inherently sensitive to. Here we directly image lattice-aperiodic valley interference between coupled atoms in silicon using sca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 75 publications
(191 reference statements)
2
31
2
Order By: Relevance
“…This onset can be measured away from a single donor as shown in Fig 3a-b. Here, it occurs at V b ∼0.2 V , which is offset compared to previous results 25,26,40 in unstrained silicon where it is found around V b ∼ − 0.8 V. This offset is attributed to an electrical short between the silicon epilayer and the handling wafer on the sample holder. Two extra resonances, at V b ∼0.6 V and V b ∼0.2 V respectively, can be observed when tunneling over a single dopant occurs (red line), which correspond to adding respectively the first (called D 0 state) and the second electron (called D − state) on the donor, the latter being close to the onset of direct transport from the valence band states 25,34 .…”
Section: Spectroscopy and Wave Function Imaging Of A Strained Donorcontrasting
confidence: 85%
See 3 more Smart Citations
“…This onset can be measured away from a single donor as shown in Fig 3a-b. Here, it occurs at V b ∼0.2 V , which is offset compared to previous results 25,26,40 in unstrained silicon where it is found around V b ∼ − 0.8 V. This offset is attributed to an electrical short between the silicon epilayer and the handling wafer on the sample holder. Two extra resonances, at V b ∼0.6 V and V b ∼0.2 V respectively, can be observed when tunneling over a single dopant occurs (red line), which correspond to adding respectively the first (called D 0 state) and the second electron (called D − state) on the donor, the latter being close to the onset of direct transport from the valence band states 25,34 .…”
Section: Spectroscopy and Wave Function Imaging Of A Strained Donorcontrasting
confidence: 85%
“…The objectives of this section are to spectroscopically evidence the presence of single donors addressable in the single electron tunneling regime, before spatially resolving their charge distribution and analysing these images in the context of the strain applied to the crystal. Donor states can be evidenced spectroscopically at 4.2 K as they yield resonances below the direct transport onset from silicon valence band states to the STM tip 25,26,40 . This onset can be measured away from a single donor as shown in Fig 3a-b.…”
Section: Spectroscopy and Wave Function Imaging Of A Strained Donormentioning
confidence: 99%
See 2 more Smart Citations
“…The results enable us to find the optimal qubit depth, which for phosphorus donors in silicon is around 2 − 2.5 nm. We note that recent studies based on STM fabrication and metrology of donor qubits have found phosphorus atoms at a similar depth range below the H-passivated surface [48,60].…”
Section: E Surface Termination and Optimal Donor Depthmentioning
confidence: 56%